Folk Dancing Documentation as a Creative Tool for Video Art - Christidis, Yiannis; Synnos, Nicos (My University, 2020)
This paper explores how both sound and image of a documentary under production footage can serve as a narrative tool for a sound-oriented video art piece (‘Folkofolk’), and at the same time communicate the ideas of the final documentary itself. It discusses possible uses of existing footage derived from an ethnographic documentary in production, which maps and records the existence of German-speaking folk dancing groups. The information of the gathered original footage seeks to understand how the notion of place is interpreted through the folk dancing soundscape as a whole, and wishes to highlight the everyday sound's social character. The footage of ‘Folkofolk’ features recordings of assorted German-speaking folk dancing groups in Berlin and Vienna. Based on the social properties of place, ‘Folkofolk’ seeks to explore, in a wider level, an alternative narrative of how folk dancing soundscapes potentially create a sense of place and community through creative film editing practices that are close to video art.
Keywords: Folk; Video art; Sound design; Composition